Glass foams from cathode-ray tubes - Barbosa, Ana (2015)
Cathode Ray Tube (CRT) waste glasses produced from dismantling TV sets were used to prepare glass foams by a simple and economic processing route, consisting of a direct sintering process of mixtures of waste glass powder (CRT) with a foaming agent (fly ashes, FA, from burning of coal). The foaming process was dependent on the composition of the mixture of raw materials (with 2 and 5 wt% FA additions) and on the sintering temperature (in the range 500 to 800 ºC). During the sintering process an oxidative reaction occurred with the release of CO2 from the foaming agent. The results allowed to study the influence of the processing conditions on the evolution of the porosity and of the pore size distribution and to analyse a relationship between these microstructural characteristics and the compressive strength of the developed materials. The objective is to produce resistant glass foams with good thermal and acoustic insulation properties that can be used as building materials. The structural glass foams produced in the present study, from the starting materials CRT and FA, can be considered as “green” alternative foams, being obtained by the recycling of two different types of wastes.